Wireless timing system using ESP-To-ESP communication protocol for precision timing in sports - Muhammad Aqib, Othman; Luqman Hakim, Amri; Muhammad Nur Fahmy, Azmi; Nur Aqilah, Othman; Mohd Hasnun Ariff, Hassan (Springer, 2024)
In a sport where determining the winner depends on milliseconds, even the slightest variation is crucial. Traditionally, stopwatches have been used for timekeeping, but this method is prone to human error when starting and stopping the timer. Therefore, a system that operates autonomously, initiating the timer through sensors and stopping it once a second or endpoint sensor detects the movement necessary to halt the timer is required. The initial sensor's interaction to start the timer will be wireless, eliminating the need for Bluetooth, which has a limited range of only 10 m. An alternative to Bluetooth is using the internet as a means of communication, but this can be problematic in areas with no internet connectivity. To compensate for the short-range limitations of Bluetooth and the absence or poor quality of an internet connection, ESP-to-ESP communication protocol is one of the options. This system enables seamless communication between the sensors and the microcontroller for initiating and displaying the timer wirelessly. Additionally, the timer will automatically stop when triggered by the sensor at the end of the competition or race, eliminating the possibility of human error in timekeeping for any time-based competition. The prototype underwent field testing in tournaments and training sessions, with over 50 uses on a single occasion.